Microwave-Induced Surface-Mediated Highly Efficient Regioselective Nitration of Aromatic Compounds: Effects of Penetration Depth - Das, Aparna; Naresh Yadav, Ram; K. Banik, Bimal (Asian Journal of Chemistry, 2021)
Surface mediated highly regioselective nitration of aromatic compounds under diverse microwave-induced conditions was investigated in this work. The effects of the penetration depth of the surfaces were found to be more crucial than other dielectric parameters. Despite significant progress of microwave-induced reactions, no reports have examined the penetration depth of the surfaces used in these processes.